Analisis SWOT Strategi Penjualan Usaha “Kopi Kenangan” - Isra Kesuma; Anggita Kumala Sari; Annisa Salsabilla; Suci Indah Sari; Ramdani Bayu Putra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Business strategy is an important part that every business person should have. This research attempts to determine the ideal strategy through SWOT analysis. The object of this study is Kenanagan Coffee. The research method used is a descriptive method with data collection techniques through Observation, Interview, and Documentation. SWOT Analysis Techniques include IFE, EFE, CPM, TOWS, IE, SPACE, Grand Strategy and QSPM. The findings of IFE Matrics and Matrics show that coffe memories has strong organizational characteristics internally with strategies that can utilize strength factors that can minimize weaknesses and be able to take advantage of opportunities from the situation faced. The analysis of TOWS Matrix, SPACE, IE, Grand Strategy as the final result of this study recommends the right business strategy for Kopi Kenanagan is to implement a market development strategy followed by product development through continuous innovation.